Profound Hypotonia and Respiratory Failure due to Suspected Nemaline Myopathy in a Preterm Infant - Gloria Akuamoah-Boateng; Raymond C. Stetson; Bethany D. Kaemingk; David A. Bieber; Jane E. Brumbaugh (Thieme Medical Publishers, Inc., 2021)
Congenital myopathies, such as nemaline myopathy, may present with hypotonia and respiratory failure in the neonatal period. Respiratory function can be further compromised in affected infants by the development of chylous effusions. We present the case of a preterm male infant born at 326/7 weeks' gestation, who was profoundly hypotonic and required intubation at birth. His clinical course progressed from acute to chronic respiratory failure with mechanical ventilation dependence. He developed bilateral chylous pleural effusions during the newborn period. Whole exome sequencing identified an ACTA1 gene mutation leading to the presumed diagnosis of nemaline myopathy. This case highlights the need to include congenital myopathies in the differential for a preterm newborn with hypotonia and respiratory failure.